Molecular and physical characterization of the complex pericentromeric heterochromatin of the vole species Microtus thomasi - Rovatsos, Michalis T; Marchal, Juan A; Romero-Fernández, Ismael; Cano-Linares, Maribel; Fernández, Francisco J; Giagia-Athanasopoulou, Eva B; Sánchez, Antonio (Cytogenetic and genome research, 2014)
A new repeated DNA from Microtus thomasi, Mth-Alu2.2, was cloned and characterized and is presented here for the first time. Digestion of genomic DNA from M. thomasi with AluI restriction enzyme revealed a 2.2-kb repetitive DNA sequence with a high AT content (69%). This sequence consists of a tandemly repeated nonanucleotide of the consensus sequence CACAATGTA, which constitutes approximately 93-95% of the total unit length. The location of the Mth-Alu2.2 sequence in the karyotype was determined by FISH, demonstrating strong hybridization signals in the pericentromeric regions of all chromosomes and in the heterochromatin blocks of several X chromosome variants. In addition, the distribution of the 4 pericentromeric repeat sequences Msat-160, Mth-Alu900, Mth-Alu2.2, and interstitial telomeric repeats was analyzed by in situ hybridization in M. thomasi, in order to shed light on the complex composition of the chromosomal pericentromeric regions in this species. The order and organization of these sequences in the pericentromeric regions are conserved, with slight variations in both the degree of overlapping and the amount of each repeated DNA in the chromosomes. Specifically, Mth-Alu2.2 is localized in the terminal regions of the chromosomes, with Msat-160 occupying the immediately inner region, partially intermixed with Mth-Alu2.2. The sequence Mth-Alu900 is found in internal positions below Msat-160, and the interstitial telomeric repeats are located close to the long-arm euchromatin of the chromosomes.
Keywords: Centrosome; Heterochromatin; buněčný rodokmen; Crosses, Genetic; repetitivní sekvence nukleových kyselin; telomery; In Situ Hybridization, Fluorescence; Female; Phenotype; Centromere; zvířata; Cell Lineage; křížení genetické; DNA; Telomere; Repetitive Sequences, Nucleic Acid; ženské pohlaví; Male; hybridizace in situ fluorescenční; Arvicolinae; fenotyp; heterochromatin; karyotypizace; Animals; centrozom; mužské pohlaví; centromera; Karyotyping